The distribution and morphology of prefrontal cortex pyramidal neurons identified using anti-neurofilament antibodies SMI32, N200 and FNP7. Normative data and a comparison in subjects with schizophrenia, bipolar disorder or major depression - Law, Amanda J.; Harrison, Paul J. (Journal of psychiatric research, 2003)
Alterations in the density and size of pyramidal neurons in the prefrontal cortex have been described in schizophrenia and mood disorder. However, the changes are generally modest and have not always been replicated. We investigated the possibility that specific pyramidal neuron sub-populations, defined by their immunoreactivity with the anti-neurofilament antibodies SMI32, N200, and FNP7, are differentially affected in these disorders. First, we assessed the distribution and characteristics of pyramidal neurons labelled by the antibodies in the human dorsolateral prefrontal cortex (Brodmann areas 9, 32, 46), using single and double label immunocytochemistry and immunofluorescence. Three largely separate sub-populations of pyramidal neurons were identified, although with more substantial overlap between SMI32- and FNP7-positive neurons in lamina V. We then determined the density, size and shape of the three pyramidal neuron sub-populations in area 9 in patients with schizophrenia, bipolar disorder, or major depressive disorder, compared to controls ( n=15 in each group). We found a lower density of lamina III N200-positive neurons in major depressive disorder than in schizophrenia or bipolar disorder. There were no other overall differences in neuronal density, or in neuronal size or shape, although a planned secondary analysis supported the previously reported decrease of neuronal size in lamina V in bipolar disorder. In summary, our study illustrates a conceptual and methodological approach which may be of value for investigating the differential neuropathological involvement of pyramidal neuron sub-populations. However, we found no clear evidence that the prefrontal neuropathology of schizophrenia or mood disorders preferentially affects SMI32-, N200- or FNP7-immunoreactive pyramidal neurons.